Zero-valent iron-activated persulfate oxidation of a commercial alkyl phenol polyethoxylate. Issue 14 (17th July 2016) - Temiz, Kubra; Olmez-Hanci, Tugba; Arslan-Alaton, Idil
ABSTRACT: Aqueous Triton X-45 (TX-45; 20 mg/L; original total organic carbon (TOC) = 14 mg/L), a representative, commercially important alkylphenol polyethoxylate, was subjected to persulfate (PS) oxidation activated with zero-valent iron (ZVI) nanoparticles. After optimization of the ZVI/PS treatment combination (1 g/L ZVI; 2.5 mM PS at pH5) in terms of pH (3–9), ZVI (0.5–5 g/L) and PS (0.5–5.0 mM) concentrations, TX-45 could be efficiently (>90%) degraded within short treatment periods (<60 min) accompanied with significant (>40%) TOC removals. The degree of PS consumption and Fe release was also followed during the experiments and a positive correlation existed between enhanced TX-45 removals and ZVI-activated PS consumption rates accompanied with a parallel Fe release. Acute toxicity tests were conducted using two different bioassays to examine the toxicological safety of the ZVI/PS oxidation system. Acute toxicity profiles significantly decreased from an original value of 66% relative inhibition to 21% and from 16% relative inhibition to non-toxic values according to Vibrio fischeri and Pseudokirchneriella subcapitata bioassays, respectively. The photobacterium V. fischeri appeared to be more sensitive to TX-45 and its degradation products than the microalgae P. subcapitata .